2010
DOI: 10.3109/10837451003774393
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of novel metronidazole sustained release and floating matrix tablets

Abstract: In the present study, metronidazole was used for preparing floating dosage forms that are designed to retain in the stomach for a long time and have developed as a drug delivery system for better eradication of Helicobacter Pylori in peptic ulcer diseases. For this means, various formulations were designed using multi-factorial design. HPMC, psyllium and carbopol in different concentrations were used as floating agents, and sodium bicarbonate was added as a gas-forming agent. Hardness, friability, drug loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…They concluded that this lasting intra-gastric buoyancy of a controlled release dosage form may also provide a suitable manner to deliver drugs that are locally active to the gastric mucosa in the stomach and, hence, achieve a sitespecific therapeutic action (e.g., antibiotic administration for H. pylori eradication in the treatment of peptic ulcer disease (Sriamornsak et al, 2004 Considering the fact that prolongation of the local availability of the antibacterial agents show positive effects of increasing in the effectiveness of H. pylori treatment ensuring a high drug concentration in the gastric mucosa, we had tried to formulate metronidazole in floating pharmaceutical dosage forms to encounter higher concentrations of the antibacterial agent in the gastric mucosa and clarify the mechanism of the release obtaining a general kinetic model for drug release profiles. In our previously published papers, we had reported the use of two different mechanisms in preparation of metronidazole floating matrix tablets including: A low density producing agent (gas generating agent/porous agent) and hydrocolloid-forming polymer(s) (Asnaashari et al, 2011). Carbonate acted as the gas generating agent when it came into contact with an acidic environment of the stomach under fed condition which got entrapped inside the system, producing bubbles, decreasing the density of the formulation.…”
Section: Floating Drug Delivery Systemsmentioning
confidence: 99%
“…They concluded that this lasting intra-gastric buoyancy of a controlled release dosage form may also provide a suitable manner to deliver drugs that are locally active to the gastric mucosa in the stomach and, hence, achieve a sitespecific therapeutic action (e.g., antibiotic administration for H. pylori eradication in the treatment of peptic ulcer disease (Sriamornsak et al, 2004 Considering the fact that prolongation of the local availability of the antibacterial agents show positive effects of increasing in the effectiveness of H. pylori treatment ensuring a high drug concentration in the gastric mucosa, we had tried to formulate metronidazole in floating pharmaceutical dosage forms to encounter higher concentrations of the antibacterial agent in the gastric mucosa and clarify the mechanism of the release obtaining a general kinetic model for drug release profiles. In our previously published papers, we had reported the use of two different mechanisms in preparation of metronidazole floating matrix tablets including: A low density producing agent (gas generating agent/porous agent) and hydrocolloid-forming polymer(s) (Asnaashari et al, 2011). Carbonate acted as the gas generating agent when it came into contact with an acidic environment of the stomach under fed condition which got entrapped inside the system, producing bubbles, decreasing the density of the formulation.…”
Section: Floating Drug Delivery Systemsmentioning
confidence: 99%
“…Peptic ulcers are sores that develop in the lining of the stomach (gastric ulcers), lower esophagus (esophageal ulcers), and/or first part of the small intestine (duodenal ulcers), as a result of inflammation caused by the bacteria H. pylori, erosions, and stomach acids. American College of Gastroenterology guidelines, 2017 for the treatment of H. pylori infection includes the following therapeutic strategies for the first-line treatment, bismuth, proton-pump inhibitors, tetracyclines, and a nitroimidazole (strong recommendation), particularly in those with previous macrolide exposure or are penicillin allergic [4]. Nitroimidazole (metronidazole) antibiotics are most active antibiotics for the treatment and prevention of infections caused by anaerobic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…carbomers) and non‐ionic (e.g. celluloses) polymers, in this regard, has extensively been employed to attain sustained release and/or gastroretention [8–15] . Accordingly, it is a challenging task to attain the desired floating‐bioadhesive potential and sustained release characteristics of the DDS using a blend of these diversely behaving polymers.…”
Section: Introductionmentioning
confidence: 99%
“…celluloses) polymers, in this regard, has extensively been employed to attain sustained release and/or gastroretention. [8][9][10][11][12][13][14][15] Accordingly, it is a challenging task to attain the desired floating-bioadhesive potential and sustained release characteristics of the DDS using a blend of these diversely behaving polymers. Systematic studies using Design of Experiments (DoE) could efficiently surmount this hiccup of balancing floatation and bioadhesion employing optimized polymer blends.…”
Section: Introductionmentioning
confidence: 99%